PENGEMBANGAN BAHAN AJAR BERORIENTASI PENDEKATAN SAINTIFIK PADA MATA KULIAH PEMBELAJARAN IPS SD DI PROGAM STUDI S1 PGSD - Wana, Prima Rias (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2017)
ABSTRACT This research had purpose to know of proper from development result of teaching material using scientific approach orientation in learning society (IPS) of Elementary School. The component validity consists of materials, presentation, languages, design, the implementation of learning, students learning outcome, and students respons.The type of this study is a research development. The development model used 4-D model (Four-D Model). The procedure is starting by defining development, design, and development. The subjects of this study are the students of S1 PGSD STKIP Modern Ngawi. 10 students (at the firts experiments ) and 32 students ( at second Experiments). Collecting data using observation, test, and questionnaires. The result of the study development result of teaching material using scientific approach orientation in learning society (IPS) of Elementary School are scoring from (1) the validity of the feasibility of component material, linguistic, and the presentation, also the validation from the experts lectur so, the module of lesson are on decent category. (2)the teaching materials from SAP implemented excellent so it can support to increased learning activities. (3) The students give positive response and the average of cognitive achievement increases. The cognitive invidual students and classical result increase its mean that its accordance with the guidelines STKIP ratings Modern Ngawi. Based on the research of result we concluded that development of teaching material using scientific approach orientation in society learning (IPS) of Elementary School were proper, practical, and effective to improve the students learning outcome in College. Keywords: Teaching Material, Scientific Approach, Society Learning (IPS). ABSTRAK Penelitian ini bertujuan untuk mengetahui kelayakan hasil pengembangan Bahan Ajar Berorientasi Pendekatan Saintifik dari validitas komponen materi, penyajian, kebahasaan, kegrafikan keterlaksanaan pembelajaran, dan hasil belajar serta respon mahasiswa. Jenis penelitian ini merupakan penelitian pengembangan. Model pengembangan yang digunakan adalah model 4-D (Four-D Model). Prosedur pengembangan dilakukan sampai tahap pendefinisian, perancangan, dan pengembangan. Subyek penelitian ini adalah mahasiswa S1 PGSD STKIP Modern Ngawi sebanyak 10 mahasiswa (ujicoba 1) dan 32 mahasiswa (ujicoba 2). Pengumpulan data menggunakan metode observasi, tes, dan angket. Hasil penelitian menunjukan bahwa data kualitas Bahan Ajar Berorientasi Pendekatan Saintifik pada Mata Kuliah Pembelajaran IPS yang dikembangkan dinilai dari (1) validitas kelayakan komponen materi, kebahasaan, penyajian serta kegrafikan dari hasil validasi yang dilakukan dosen ahli dengan kategori sangat layak. (2) bahan ajar dari keterlaksanaan SAP yang dilaksanakan dosen sangat baik yang mendukung peningkatan kegiatan pembelajaran. (3) respon mahasiswa ditanggapi dengan positif dan rata-rata hasil belajar kognitif meningkat. Ketuntasan hasil belajar mahasiswa secara individu maupun klasikal dapat tuntas sesuai dengan pedoman penilaian STKIP Modern Ngawi. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa pengembangan Bahan Ajar Berorientasi Pendekatan Saintifik pada Mata Kuliah Pembelajaran IPS SD layak untuk meningkatkan hasil belajar kognitif mahasiswa di perguruan tinggi. Kata Kunci : Buku Ajar, Pembelajaran Saintifik , Pembelajaran IPS SD.